Improved Myocardial Perfusion Imaging Accuracy: The Benefits of Combined Supine and Prone Acquisition - Seher, Saima (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess whether prone imaging enhances attenuation correction (AC), thereby improving the specificity and overall diagnostic accuracy of myocardial perfusion imaging (MPI) without compromising sensitivity.Study Design: Analytical Cross-sectional study.Place and Duration of Study: Nuclear Department, Army Cardiac Hospital Lahore; from Dec 2023-Jun 2024.Methodology: One hundred and twenty four patients with fixed or reversible inferior wall perfusion abnormalities and suspected or proven ischemic heart disease were included in the study using non-probability sequential sampling. All patients underwent supine stress/rest SPECT MPI followed by additional stress prone SPECT. Patients with normal MPI and normal perfusion of inferior wall were excluded. Diagnostic accuracy of prone imaging against the coronary artery disease (CAD) was determined based on sensitivity and specificity.Result:  The mean age of the 124 patients who were enrolled was 57.2±11.3 years; 86(69.4%) of them were men. The mean LVEF was 54.4±7.8%, and the mean BMI was 26.6±3.0 kg/m². Among the patients, 69.4% had hypertension and 68.5% had diabetes mellitus. Prone MPI showed an overall accuracy of 78.0%, sensitivity of 64.2%, specificity of 87.7%, positive predictive value of 86.0%, and negative predictive value of 67.6%. Accuracy for supine fixed perfusion abnormalities was 74.0%, but accuracy for reversible defects was 75.0%. Consequently, prone imaging demonstrated a more reliable and balanced diagnostic performance for the detection of CAD.Conclusion: Combining MPI with prone and supine imaging improved diagnostic accuracy and specificity without compromising sensitivity.